(3bhGYO GdTQjYIs - (3YR GdOjf YHO GdYRjR Hf YHO GdSdGe Hf CHj GdbGSe GdTGaYj GdSdej GdOeTbj GdeUQj, SdWGf GdYdeGA YR GdOjf Hf YHO GdSdGe,J (B660 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe YR GdOjf CHh eMeO YHO GdYRjR Hf YHO GdSdGe s
(3BNQgG (B:s
(3Je cJGH bhGYO GdTQjYIq s
(3GdfSNI HgG MhGTs
(3HgG WjGQGJs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B144s
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs